DEVELOPMENT AND INTEGRATION PLAN OF MATO GROSSO DO SUL’S BORDER STRIP: A VIEW FROM THE ECONOMIC INDICATORS - Boldrine Abrita, Mateus; Heloiza Conte, Cláudia (GEOFRONTER, 2023)
The Development and Integration Plan of the Border Strip of the State of Mato Grosso do Sul - PDIF/MS (2012) was developed. This Plan presented seven strategic axes and the purpose of this paper is to specifically analyze the axis "economic development" to verify the monitoring of the results concerning the established goals. For this, data and socioeconomic and development indicators will be collected. The method will be based on the analysis of descriptive statistics as well as stylized facts. After analyzing the data and indicators, it was pointed out that important improvements occurred in the agricultural sector and storage. But on the other hand, few advances were observed in industrial diversification. Regarding tourism, trade, and services, there have been advances concerning the goals, however, it is important to emphasize that the goals established in the PDIF/MS are not specific, measurable, achievable, relevant, and temporal (SMART), consequently, performance evaluation is difficult. However, it is essential to develop a new Development and Integration Plan for the State of Mato Grosso do Sul’s Border Area that in fact will be able to provide SMART goals, for effective monitoring and of the Plan, and for its results to be robust and significant.